PENGARUH BUKAAN SUDU PENGARAH TERHADAP AIR PADA TURBIN DI PLTA PARAKAN KONDANG - Nurus Saparudin, Rifki; Dewi Jannati, Eidelweis; Budiman, Haris (Universitas Majalengka, 2019)
The problem that often occurs in Hydroelectric Power Plant (HPP) is erratic water discharge in the reservoir so that variations in blade openings can be carried out in order to stabilize the flow of water entering the turbine. The occurrence of this problem will result in a decrease in turbine efficiency. Different causes - the difference is the variation of the guide blade opening also aims to stabilize the turbine rotation. variation of the guide blade opening and turbine shaft rotation as the independent variables namely ¾, ½, 1/3 and full openings, then for the rotation are 598, 560, 545 and 600 rpm. The efficiency produced at full openings is 93.35%, openings ¾ are 93.04%, openings ½ are 87.13% and openings 1/3 are 84.79%. So it can be concluded that the full openings have the highest efficiency.